Kualitas Pelayanan Dinas Tenaga Kerja Kabupaten Purbalingga dalam Pembuatan Kartu Tanda Pencari Kerja - Muhammad Danang V T; Hanny Purnamasari; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study discusses the service quality of the Manpower Office of Purbalingga Regency in making job seeker ID cards. This study uses Zaithml's theory of service quality (Jayanti, 2016) which has five variable dimensions, namely Reliablility, Responsiveness, Assurance, Empathy and Tangibles. The method used in this research is qualitative. Data collection techniques were carried out through interviews, observations and documentation studies which were then analyzed in three stages, reduction, presentation and drawing conclusions. The results of this study indicate that the service quality of the Manpower Office of Purbalingga Regency in making job seeker ID cards is still not optimal from all dimensions where the reliability of employees in implementing the service quality of making job seeker ID cards is not in accordance with applicable SOPs. Responsiveness of many employees who are not placed according to their expertise and graduates. Assurance does not have a guarantee and the 5S principle does not apply at the Manpower Office of Purbalingga Regency. Empathy, there are still many employees who are apathetic to public complaints. Tangibles still found inadequate or damaged infrastructure.